2023
DOI: 10.1002/bmm2.12046
|View full text |Cite
|
Sign up to set email alerts
|

Advanced strategies of scaffolds design for bone regeneration

Jian Song,
Longfei Li,
Lei Fang
et al.

Abstract: Bone defects are encountered substantially in clinical practice, and bionic scaffolds represent a promising solution for repairing bone defects. However, it is difficult to fabricate scaffolds with bionic structures and reconstruct the microenvironment to fulfill the satisfying repair effects. In this review article, we first discuss various strategies for the design and construction of bionic scaffolds to promote bone defect repair, especially including the structural construction of the scaffold and the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 187 publications
(347 reference statements)
2
8
0
Order By: Relevance
“…In addition, there existed no pathological abnormalities in the liver and kidney tissues of rats with implantation of piezoelectric membranes and application of US treatment, suggesting the excellent biocompatibility of the therapeutic system discussed above (Figure S7C). Previous efforts have been made to promote macrophage M2 polarization for improved bone regeneration. However, recent works further revealed that sequential macrophage transition based on the temporal immune orchestration would achieve optimized osteogenesis, as overinhibition of initial inflammation would destroy the natural transition of the macrophage phenotype during bone regeneration. Our findings further confirmed that precise control of the M1-to-M2 transition coordinated with a natural process could result in a promising diabetic bone repair outcome. Considering the similar pathological features of other tissue defects, including nerve, skin, and cartilage, under a diabetic background (high ROS accumulation and excessive pro-inflammatory status), application of temporal immunomodulation might also be expanded to other clinical situations.…”
Section: Resultssupporting
confidence: 71%
“…In addition, there existed no pathological abnormalities in the liver and kidney tissues of rats with implantation of piezoelectric membranes and application of US treatment, suggesting the excellent biocompatibility of the therapeutic system discussed above (Figure S7C). Previous efforts have been made to promote macrophage M2 polarization for improved bone regeneration. However, recent works further revealed that sequential macrophage transition based on the temporal immune orchestration would achieve optimized osteogenesis, as overinhibition of initial inflammation would destroy the natural transition of the macrophage phenotype during bone regeneration. Our findings further confirmed that precise control of the M1-to-M2 transition coordinated with a natural process could result in a promising diabetic bone repair outcome. Considering the similar pathological features of other tissue defects, including nerve, skin, and cartilage, under a diabetic background (high ROS accumulation and excessive pro-inflammatory status), application of temporal immunomodulation might also be expanded to other clinical situations.…”
Section: Resultssupporting
confidence: 71%
“…The experimental H-SLM implant had been widely reported as a promising design of dental implants with quick osseointegration. ,, This work supported the current knowledge that macrophage polarization can influence the fate of mesenchymal stem cells. Further, this work complemented it with the anti-inflammatory effect of blood clots, as the microenvironment around implants can affect bone formation . In previous studies, the immunomodulation effect of hydrophilic implants was mostly investigated in surface cultured cells, and macrophages cultured on hydrophilic implant surfaces tended to polarize as M2-phenotype for anti-inflammation. , However, the limitations of surface cell culture had been gradually thought highly since 2003 due to the lack of microenvironment .…”
Section: Resultssupporting
confidence: 68%
“…Biomedical materials are materials used in medicine, including sensing, detection, diagnosis, therapy, tissue repair, organ regeneration, in situ cell therapy, vascularization in the organoid vascularization, etc. Bone defect repair has also received much attention in recent years. Especially in organoid research and sensing analysis, biomedical materials have become an important branch of modern materials science. , With the booming development of biotechnology and the increasing improvement of health requirements, more and more biomedical materials such as graphene, , metal–organic frameworks (MOFs), maximally exfoliated two-dimensional carbides and nitrides (MXenes) and layered double hydroxide (LDH) have been discovered and are receiving extensive attention from scientists. Although, considerable progress has been made over the decades, some biomaterials present problems such as difficult preparation, high cost, poor biocompatibility and tolerability, which limit further applications in the treatment of diseases such as cancer, cardiovascular diseases, obesity, chronic diseases and, etc .…”
Section: Introductionmentioning
confidence: 99%